The Effects of Simvastatin and Soursop (Annona muricata) Leaf Extract on Colorectal Cancer - Amadea, Ignatia Ceraphine; Atrasina, Dina (Indonesian Journal of Life Sciences, 2021)
Colorectal cancer (CRC) is a heterogeneous disease of the colon and rectum. In Indonesia, CRC has the fourth highest cancer incidence, with about 30,000 new cases and causing around 16,000 deaths per year. Numerous studies have shown the benefits of using simvastatin and Annona muricata (A. muricata) leaf extract to promote cytotoxic effects in CRC cells. This systematic review aimed to evaluate the effects and the possible molecular mechanisms of actions used by simvastatin and A. muricata leaf extract to exert anti-cancer effects in CRC cells. We synthesized published studies on the effect of simvastatin and A. muricata leaf extract in in vitro and in vivo CRC studies, and highlighted the potential application of simvastatin and A. muricata leaf extract in combination with other anti-cancer treatments. This systematic review was written in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Simvastatin and A. muricata leaf extract were shown to suppress CRC cell growth and proliferation and generate a synergistic effect when combined with other anti-cancer treatments. Several possible mechanisms of actions of simvastatin include bone morphogenetic protein (BMP) pathway and mevalonate pathway activation, ERKs inactivation, and regulation of the yes-associated protein 1 (YAP1), while for A. muricata leaf extract, possible mechanisms of actions include intrinsic apoptosis pathway activation, cytochrome c-mediated apoptosis, mitochondria-mediated apoptosis, and programmed cell death initiation. Further experimental evidence is needed to determine the specific mechanisms on how simvastatin and A. muricata leaf extract induce anti-cancer effects against CRC cells.